EVALUACIÓN DEL VALOR NUTRICIONAL DE PASTO JANEIRO (Erioclhoa polystachya Kunth) M2 IRRADIADO CON RAYOS GAMMA, CON DIFERENTES INTERVALOS DE CORTE - Tierra Cedeño, Fanny Elizabeth (2020)
The janeiro grass (Eriochloa polystachya Kunth) is a species used in forage with appropriate characteristics to thrive in marginal conditions that needs to be improved in its nutritional value or other agronomic characteristics. Gamma rays can be used for the genetic improvement of plants and generate mutations that can be useful. The investigation was carried out with the objective of determining the best cutting season. The study was carried out in the field of the Faculty of Agricultural Sciences of the Technical University of Babahoyo. Five doses were evaluated 0; 25; 50; 75 and 100 Co60 gamma ray gray. Two cutting times 25 and 40 days after the equalization cut and two doses of fertilization with N-P-K were evaluated. A randomized complete block design with factorial arrangement (DBCA) was used, which was contrasted with the Tukey test at 95% probability, with the InfoStat statistical package. The dry matter percentages were 26.48 at 25 days and 22.25 at 40 days, the averages were for branch length 1.94 meters, leaf length and leaf width 30.76 cm and 1.82 cm respectively, the best percentage of protein being I present the witness with 12.29%